2017
DOI: 10.1016/j.flm.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Parallel pathogens in the upper and lower respiratory tracts in children with a respiratory tract infection, as revealed by the Filmarray assay

Abstract: a b s t r a c tBackground: Respiratory tract infection (RTI) is a common disease among children of all ages that causes high hospitalization and mortality rates. Infection with more than one pathogen has been reported in RTI; however, the association of the pathogen spectrum in upper and lower respiratory tract infections remains unclear. Methods: A prospective study was conducted during February to October 2016. Fifty-five nasopharyngeal swabs (NPS) and 30 bronchoalveolar lavage fluid (BALF) samples from 55 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…To our knowledge, no previous study had reported these results, and further investigations are required. The rest of our findings are in line with the previous studies, mostly nasopharyngeal swab and BAL results [ [10] , [11] , [12] , [13] ].…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, no previous study had reported these results, and further investigations are required. The rest of our findings are in line with the previous studies, mostly nasopharyngeal swab and BAL results [ [10] , [11] , [12] , [13] ].…”
Section: Discussionsupporting
confidence: 93%